Does rehabilitation improve work participation in patients with chronic spinal pain after spinal surgery: a systematic review - Jonas Callens; Olivia Lavreysen; Lisa Goudman; Ann De Smedt; Koen Putman; Dominique Van de Velde; Lode Godderis; Dries Ceulemans; Maarten Moens (Journal of Rehabilitation Medicine, 2025)
Objective: Patients with therapy-refractory chronic spinal pain after spinal surgery experience increased disability, resulting in substantial loss of employment and consequently lower quality of life. Despite findings that rehabilitation improves socio-economic outcomes in other chronic pain conditions, evidence for patients with chronic spinal pain after spinal surgery is limited. A systematic review was conducted to provide an overview of rehabilitation interventions and their effectiveness to improve work participation for patients with chronic spinal pain after spinal surgery.